KARAKTERISTIK PEMBAKARAN DROPLET DENGAN VARIASI KOMPOSISI CAMPURAN BENSIN - ETANOL - Arwin, Arwin; Yuliati, Lilis; Widodo, Agung Sugeng (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
The objective of this research is to investigate the droplet combustion characteristics of gasoline-ethanol fuel blended. The combustion characteristics included ignition delay time, burning lifetime, burning rate constant, flame height, flame temperature, and microexplosion. Testing was conducted using fuel blended with ethanol percentage of 0%(E0), 10%(E10), 20% (E20), 30% (E30) and 100% (E100). The fuel was dripped on the tip of the thermocouple junction and ignited using a torch of a butane-air mixture on a cylindrical burner. The results showed that the ignition delay time increase with the increase of ethanol percentage due to its high latent heat of evaporation and flash point temperature. However, flame temperature decrease with the increase of ethanol percentage due to the lower heat release rate of the mixture, related to the lower heating value of ethanol, and the burning rate constant of the fuels were not different significantly. The droplet diameter of the E100 (pure ethanol) decrease according to the d2?law, but the droplet diameters of the E0, E10, E20, and E30 changed drastically, exhibiting expansion and shrinkage. The Combustion of E20 fuel droplet has the highest burning rate constant, and flame height due to the oxygen content in ethanol can accelerate the combustion reaction and the fastest fuel droplet evaporates and diffuses into the air. Besides, the combustion of the E20 fuel droplet has the lowest burning lifetime due to the intensity of the microexplosion often makes the fuel droplet break into small droplets, which helps accelerate the process of evaporation and mixing of fuel with air, so that the combustion reaction occurs faster. Microexplosionphenomenon also identified due to the difference between the boiling point temperature gasoline and ethanol.